Highlights of recent IFPRI research and partnerships in Bangladesh: Reducing poverty and hunger through food policy research - International Food Policy Research Institute (International Food Policy Research Institute, 2016)
For more than two decades, IFPRI’s research and policy analysis have been a resource for Bangladesh in making impressive strides in ensuring food security and reducing poverty. Working closely with the Bangladesh Ministry of Food and Disaster Management and its Food Planning and Monitoring Unit, the Ministry of Agriculture, the Bangladesh Institute of Development Studies, BRAC, CARE International, and civil society organizations, IFPRI has supported Bangladesh in its goals of improving nutrition, women’s empowerment, social protection, and coping with natural disasters. IFPRI looks forward to deepening its collaboration with these and other partners through its Policy Research and Strategy Support Program and complementary initiatives, and to enhancing long-term capacity in policy analysis and evidence-based research. Such strong collaborative efforts have translated and will continue to translate research into policy action that will help accelerate Bangladesh’s progress in ending hunger and undernutrition.